O uso de técnicas de gamificação como auxílio a resolução de problemas no campo da análise combinatória - Aguiar, Igor Pereira (2019)
The current scenario of mathematics in Brazil consists of students who have one of the worst school performance in global scale. The present work was developed with the purpose of elaborating an educational product that helps the teaching and learning of mathematics, adopting the combinatorial analysis study area. It was observed data that show that smartphones and tablets have become very popular in recent years, for example, we have in Brazil more active smartphones than the number of Brazilians. We also analyze data that show that our young people have a certain fascination with digital games. Based on this information the strategy of creating a prototype for smartphones was adopted, in which gamification techniques were used to motivate and engage the student in the teaching of combinatorial analysis, using as pedagogical guiding theory Polya’s problem solving techniques. To validate the objectives of this study, a evaluation was carried out with high school students of the Ayrton Senna da Silva School, a school located in the central zone of Boa Vista, Roraima. Before and after the use of the prototype, questionnaires were distributed to students and some education professionals and with the collection of data obtained it was possible to carry out a brief analysis on some aspects of this research, such as: ease in handling the application, fixing contents, among others. This analysis led us to verify that the development of the prototype contributed with positive gains for the teaching of mathematics.